2022
DOI: 10.1186/s40035-022-00307-z
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic acid: a potential therapeutic tool in neurodegenerative diseases

Abstract: Most neurodegenerative disorders are diseases of protein homeostasis, with misfolded aggregates accumulating. The neurodegenerative process is mediated by numerous metabolic pathways, most of which lead to apoptosis. In recent years, hydrophilic bile acids, particularly tauroursodeoxycholic acid (TUDCA), have shown important anti-apoptotic and neuroprotective activities, with numerous experimental and clinical evidence suggesting their possible therapeutic use as disease-modifiers in neurodegenerative diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 105 publications
(148 reference statements)
2
33
0
Order By: Relevance
“…This corresponds to a prolongation of median survival by 4-5 months. This indication of efficacy is further supported by the evidence that TUDCA has cytoprotective properties in animal models of different neurodegenerative diseases (5). Recently, another phase II trial on TUDCA Abbreviations: ALS, amyotrophic lateral sclerosis; ALSAQ , ALS Assessment Questionnaire-; ALSFRS-R, ALS functional rating scalerevised; CRO, contract research organization; CSF, cerebrospinal fluid; eCRF, electronic case report form; EQ-D-L, EuroQol -Dimension-L; FVC, forced vital capacity; GCP, good clinical practice; IMP, investigational medicinal product; IIH, Italian Institute of Health; ITT, intention to treat; MMP-, matrix metalloproteinase-; MRC, Medical Research Council; NFL, neurofilament light chain; pNFH, neurofilament heavy chain; SOPs, standard operating procedures; TUDCA, tauroursodeoxycholic acid; UDCA, ursodeoxycholic acid.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…This corresponds to a prolongation of median survival by 4-5 months. This indication of efficacy is further supported by the evidence that TUDCA has cytoprotective properties in animal models of different neurodegenerative diseases (5). Recently, another phase II trial on TUDCA Abbreviations: ALS, amyotrophic lateral sclerosis; ALSAQ , ALS Assessment Questionnaire-; ALSFRS-R, ALS functional rating scalerevised; CRO, contract research organization; CSF, cerebrospinal fluid; eCRF, electronic case report form; EQ-D-L, EuroQol -Dimension-L; FVC, forced vital capacity; GCP, good clinical practice; IMP, investigational medicinal product; IIH, Italian Institute of Health; ITT, intention to treat; MMP-, matrix metalloproteinase-; MRC, Medical Research Council; NFL, neurofilament light chain; pNFH, neurofilament heavy chain; SOPs, standard operating procedures; TUDCA, tauroursodeoxycholic acid; UDCA, ursodeoxycholic acid.…”
Section: Introductionmentioning
confidence: 68%
“…This corresponds to a prolongation of median survival by 4–5 months. This indication of efficacy is further supported by the evidence that TUDCA has cytoprotective properties in animal models of different neurodegenerative diseases ( 5 ). Recently, another phase II trial on TUDCA combined with sodium phenylbutyrate showed a positive effect on disease progression, further supporting a possible role of TUDCA in reducing ALS progression ( 9 ).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations